IMAGE RESTORATION AND ITS EFFECTIVENESS OF VARIOUS BLIND IMAGE DECONVOLUTION ALGORITHMS - VISHWABRAHMA SHILPA S.K. TYAGI, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Motion blur is an inevitable tradeoff between the amount of blur and the amount ofnoise in the acquired images. The effectiveness of any restoration algorithm typically dependson these amounts, and it is difficult to find their best balance in order to ease the restoration task. The Point-Spread-Function (PSF) trajectories